2017
DOI: 10.1158/2159-8290.cd-17-0419
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Somatic Mutations Restoring RAD51C and RAD51D Associated with Acquired Resistance to the PARP Inhibitor Rucaparib in High-Grade Ovarian Carcinoma

Abstract: High-grade epithelial ovarian carcinomas containing mutated BRCA1 or BRCA2 (BRCA1/2) homologous recombination (HR) genes are sensitive to platinum-based chemotherapy and PARP inhibitors (PARPi), while restoration of HR function due to secondary mutations in BRCA1/2 has been recognized as an important resistance mechanism. We sequenced core HR pathway genes in 12 pairs of pretreatment and postprogression tumor biopsy samples collected from patients in ARIEL2 Part 1, a phase II study of the PARPi rucaparib as tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
256
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 340 publications
(283 citation statements)
references
References 48 publications
7
256
0
Order By: Relevance
“…As PARPi are increasingly being used for cancer therapy, understanding their resistance is becoming more and more significant and urgent. In fact, clinical resistance to PARPi, including olaparib, rucaparib and veliparib, has been reported. In addition, PARPi will probably extend their application to non‐BRCA/ATM‐mutated cancers .…”
Section: Discussionmentioning
confidence: 99%
“…As PARPi are increasingly being used for cancer therapy, understanding their resistance is becoming more and more significant and urgent. In fact, clinical resistance to PARPi, including olaparib, rucaparib and veliparib, has been reported. In addition, PARPi will probably extend their application to non‐BRCA/ATM‐mutated cancers .…”
Section: Discussionmentioning
confidence: 99%
“…The genomic instability of all HGSOCs and the deficiency in DNA repair in almost 50% of HGSOCs are vulnerabilities that have allowed susceptibility to platinum chemotherapy and PARP inhibitors. Tumor and circulating cell‐free DNA (cfDNA) analyses now demonstrate evolutionary adaptation in response to platinum chemotherapy and PARP inhibitors and, in some patients, result in the emergence of bridging reversion mutations, whereas in other patients they lead to multiple parallel mutations, which overcome the prior therapeutic vulnerability and confer resistance …”
Section: Improving Outcomesmentioning
confidence: 99%
“…Tumor and circulating cell-free DNA (cfDNA) analyses now demonstrate evolutionary adaptation in response to platinum chemotherapy and PARP inhibitors and, in some patients, result in the emergence of bridging reversion mutations, whereas in other patients they lead to multiple parallel mutations, which overcome the prior therapeutic vulnerability and confer resistance. 117,152…”
Section: Sensitivity and Resistance To Therapymentioning
confidence: 99%
“…Secondary mutations were also identified that same year in platinum-resistant BRCA1 -mutated ovarian cancers (185delAG and 2594delC) (Swisher et al 2008). BRCA1 and BRCA2 secondary mutations continue to be reported in multiple cancer types (e.g., Afghahi et al 2017, Pishvaian et al 2017) and, more recently, in other HDR pathway genes, in particular, the RAD51 paralog genes RAD51C and RAD51D (Kondrashova et al 2017). …”
Section: Mechanisms Of Resistance To Poly(adp-ribose) Polymerase Imentioning
confidence: 99%